STUDI EMPIRIS MANAJEMEN PENGELOLAAN TABUNGAN PADA GENERASI MILENIAL DI KOTA BATAM - Yuwono, Wisnu (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
The purpose of this study is to determine the variables that are thought to strongly influence the management of savings management on the millennial generation in Batam City. Batam City is an industrial and trade city whose geographical location is in direct line with Singapore and Malaysia, offering a lot of very attractive goods and services, especially for millennials. The variables used are self-control, attitude toward saving, financial literacy, parental socialization, and peer influence on saving behavior. The methodology in this study uses primary data through the distribution of questionnaires to 267 millennial respondents, and processing the data using the SPSS program version 21.0, the results show that the attitude toward saving, financial literacy, parental socialization variables have a significant effect on the saving behavior variable, but the variable self-control, and peer influence do not have a significant influence on saving behavior in the millennial generation of Batam City.